Особливості біометричних показників зорового аналізатора у дітей із набутою міопією, асоційованою із синдромом недиференційованої дисплазії сполучної тканини - Цибульська, Таміла Євгенівна; Завгородня, Наталія Григорівна; Пашкова, Олена Єгорівна; Цыбульская, Т. Е.; Завгородняя, Н. Г.; Пашкова, Е. Е.; Tsybulska, T. E.; Zavgorodnya, T. S.; Pashkova, O. E. (My University, 2018)
Мета роботи: оцінити біометричні показники зорового аналізатора у дітей із набутою міопією, асоційованою з синдромом недиференційованої дисплазії сполучної тканини. Встановлено деякі особливості біометричних показників зорового аналізатора у дітей з міопією на тлі сполучнотканинної дисплазії, які виявляються у зниженні сили заломлення рогівки в середньому на 4,6 %, збільшенні радіуса кривизни на 5,3 % та діаметра рогівки на 7,2 %, збільшенні глибини передньої камери ока в середньому на 5,2 %, сагітальної довжини склоподібного тіла в середньому на 9,2 % та аксіальної довжини ока в середньому на 4,2 %. Цель работы – оценить биометрические показатели зрительного анализатора у детей с приобретенной миопией, ассоциированной с синдромом недифференцированной дисплазии соединительной ткани. Выявлены особенности биометрических показателей зрительного анализатора у детей с миопией на фоне соединительнотканевой дисплазии, которые заключаются в снижении преломляющей силы роговицы в среднем на 4,6 %, увеличении радиуса кривизны на 5,3 % и диаметра роговицы на 7,2 %, увеличении глубины передней камеры глаза в среднем на 5,2 %, сагитальной длины стекловидного тела в среднем на 9,2 % и аксиальной длины глаза в среднем на 4,2 %. Myopia is one of the major visceral manifestations of the syndrome of undifferentiated dysplasia of connective tissue. The aim of the research is to evaluate the biometric characteristics of the visual analyzer in children with acquired myopia associated with syndrome of undifferentiated dysplasia of connective tissue. Group I consisted of 44 examined children (88 eyes) with myopia and manifestations of connective tissue dysplasia, group II – 40 children (80 eyes) with myopia and without phenotypic manifestations of dysplasia. The presence of phenotypic signs of dysplasia in accordance with the diagnostic criteria of T. Milkovska-Dimitrova and A. Karkasheva. The ophthalmic examination included measurement of the refractive corneal force, cornea diameter, corneal curvature radii, corneal thickness, anterior chamber depth, lens thickness, sagittal length of the vitreous body, axial length of the eye. Reliable differences in the groups were obtained between the index of refractive corneal force: in group I – 41.25 (40.62–41.75) dpt, in group II – 43.25 (42.75–43.75) dpt; between the radius of the cornea: in group І – 8.13 (7.97–8.28) mm, in group II – 7.7 (7.5–7.8) mm; between the diameter of the cornea in group I – 12.4 (12.1–12.7) mm, in group II – 11.5 (11.3–11.6) mm; between the depth of the anterior chamber: in group І – 3.8 (3.4–4.0) mm, in group II – 3.6 (3.4–3.7) mm; between the sagittal length of the vitreous body: in group I – 17.5 (17.3–18.0) mm, in group II – 15.9 (15.4–16.1) mm; between the axial length of the eye: in group I – 24.9 (24.4–25.4) mm, in group II – 23.9 (23.4–24.5) mm (p<0.05). Positive reliable correlation was found between the magnitude of the radius of the cornea and the degree of dysplasia (r=0.35, p<0.05), as well as between the diameter of the cornea and the degree of dysplasia (r=0.44, p<0.05), between the depth of the anterior the camera and the degree of dysplasia (r=0.41, p<0.05), between the axial length of the eye and the degree of dysplasia (r=+0.43, p<0.05). Thus, in children with myopia associated with the syndrome of undifferentiated connective tissue dysplasia, unlike children with myopia without signs of dysplasia, we revealed features of biometric indicators that consist in reducing the corneal force of refraction by an average of 4.6%, an increase in the radius of curvature by 5.3% and corneal diameter by 7.2%, an increase in the depth of the anterior chamber of the eye, on average, by 5.2%, sagittal length of the vitreous body, on average, by 9.2%, and an axial length of the eye, on average, by 4.2%. The obtained data can be useful for diagnosing the prognosis of myopic process and determining the individual treatment tactics.
Особенности биометрических показателей зрительного анализатора у детей с приобретенной миопией, ассоциированной с синдромом недифференцированной дисплазии соединительной ткани
Features of the biometric indicators of the visual analyzer in children with acquired myopia associated with the syndrome of undifferentiated dysplasia of connective tissue
Keywords: міопія; діти; біометричні показники; дисплазія сполучної тканини; миопия; дети; биометрические показатели; дисплазия соединительной ткани; myopia; children; biometric indicators; connective tissue dysplasia